MAKER CULTURE IN EDUCATION: FOUNDATIONS, POTENTIAL, AND CHALLENGES FOR PEDAGOGICAL INNOVATION - Borges, Martinha Luiza Rolim de Moura (Seven Editora, 2026)
This article aims to present a literature review on Maker Culture in Education, based on journal articles and books, constituting a bibliographic research. It explores the fundamental concepts and characteristics of Maker Culture, its relevance to the educational environment, and practical examples of its application, aiming to show how this approach can contribute to innovative pedagogical practices and educational strategic planning. Maker Culture is a movement that values people's autonomy and creative capacity to solve everyday problems, regardless of their background. In education, it is based on Papert’s constructionism, prioritizing student protagonism in practical and collaborative projects, which transforms the dynamics of pedagogical practices, making them more active and meaningful. Maker Culture has proven to be a promising approach by enriching the school curriculum with practices that promote creativity, problem solving, use of technologies, and meaningful learning. It is concluded that, although its implementation faces challenges such as scarcity of resources, limited infrastructure, and the need for teacher training, the positive results observed indicate that Maker Culture can transform schools into more innovative, inclusive spaces aligned with contemporary demands of teaching and learning.DOI: https://doi.org/10.56238/sevened2026.001-005